Korrelatsionnyi analiz otdel'nykh pokazatel'ei kardio-respiratornoi sistemy dlya byyavleniya stress-sostoyanii - Isayev, A. P.; Bykov, E. V.; Kabanov, S. A. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The aim of this study was to reveal the opportunities of K.V. Sudakov's method of the stress-state evaluation with a help of cross-correlative analysis. The influence of success and failure on the dynamics of stress-state in elite wrestlers (n=22) aged from 20 to 28 had been investigated. As a result of the research it had been concluded that the "successful" subject were more capable for adaptation to stress influences. The athletes suffered by the failure had no the correlative dependences between the indicies of their cardiorespiratory system. The obtained data show the opportunity to use this methodics for noninvasive diagnosis of the athletes functional system's stress at the period of urgent and permanent adaptation.